Better Rebuilding Mechanisms for Villages in Central and Northern Syria Using Domed and Treated Mud - Bezzi, Zakaria Abdulrahman; Zeitoun, SaadEldin AlaaEldin; Malandi, Hala HussamEddin (Journal of engineering sciences and information technology, 2022)
This research studies the mud villages and the domed mud rural house in Syria, which over decades represented an important part of the traditional architectural identity of the Syrian countryside and an in the arid regions of Syria with a harsh climate and difficult living conditions, and the research identifies its problem in the gradual deterioration of these mud houses due to the transformation in their architectural style and the abandonment of traditional mud models, in addition the war in Syria increased this deterioration through the migration of these, Therefore, this research aims to limit this deterioration by setting scientific design directions for building the contemporary rural dwellings in the domed mud villages to comply with their specificity and architectural character, with the variables of the current era and the new aspirations of the villager. The research relied on several interrelated scientific methodologies: a theoretical approach that studies the design features of these homes, and an analytical approach to reach the most important architectural features of these homes. And then an applied approach through the study of applied cases and models from the studied area in the countryside of Aleppo Governorate. The research concluded that the traditional housing in these villages is a state of great compatibility with the various spatial and temporal characteristics of its residents, with the presence of a number of weaknesses in its design structure, most notably the weakness of the clay material in front of weather factors, which requires continuous periodic maintenance, and the research recommended continuing with the domed mud house model as a tool for reconstruction in these villages, with developments being carried out on this dwelling to become more environmentally, socially, economically and structurally sustainable.